Boletus aereus protects against acute alcohol-induced liver damage in the C57BL/6 mouse via regulating the oxidative stress-mediated NF-κB pathway - Luping Zhang; Bo Meng; Lanzhou Li; Yanzhen Wang; Yuanzhu Zhang; Xuexun Fang; Di Wang (Taylor & Francis Group, 2020)
Context Alcoholic liver disease, caused by abuse and consumption of alcohol, exhibits high morbidity and mortality. Boletus aereus Bull. (Boletaceae) (BA) shows antioxidant, anti-inflammatory and antimicrobial effects. Objectives To investigate the hepatoprotective effects of BA using an acute alcohol-induced hepatotoxicity mice model. Materials and methods The composition of BA fruit body was first systematically analyzed. Subsequently, a C57BL/6 mice model of acute alcohol-induced liver injury was established by intragastrically administration of alcohol, which was intragastrically received with BA powder at 200 mg/kg and 800 mg/kg for 2 weeks, 60 mg/kg silybin treatment was used as positive control group. By employing the pathological examination, ELISA, RT-PCR and western blot, the regulation of BA on oxidative stress signals was investigated. Results The LD50 of BA was much higher than 4 g/kg/p.o. In acute alcohol-damaged mice, BA reduced the levels of alanine aminotransferase (>18.3%) and aspartate aminotransferase (>27.6%) in liver, increased the activity of liver alcohol dehydrogenase (>35.0%) and serum acetaldehyde dehydrogenase (>18.9%). BA increased the activity of superoxide dismutase (>13.4%), glutathione peroxidase (>11.0%) and 800 mg/kg BA strongly reduced chemokine (C-X-C motif) ligand 13 (14.9%) and chitinase-3 like-1 protein (13.4%) in serum. BA reversed mRNA over-expression (>70%) and phosphor-stimulated expression (>45.0%) of an inhibitor of nuclear factor κ-B kinase (NF-κB, an inhibitor of nuclear factor κ-B α and nuclear factor κ-B in the liver. Conclusions BA is effective in ameliorating alcohol-induced liver injury through regulating oxidative stress-mediated NF-κB signalling, which provides a scientific basis for further research on its clinical applications.